Imprecise probability analysis of steel structures subject to atmospheric corrosion. (July 2017) - Zhang, Hao; Ha, Loc; Li, Quanwang; Beer, Michael
Highlights: Significant epistemic uncertainties exist in the current models for atmospheric corrosion of steels. Epistemic uncertainties are modeled by dependent probability-boxes. Dependence between probability-boxes is described by copulas. Epistemic uncertainties play an important role in the time-dependent reliability of deteriorating steel structures. Ignoring the effects of epistemic uncertainty may lead to a false impression of the reliability. Abstract: Evaluating the behaviour of deteriorating steel structures is complicated by the inherent uncertainties in the corrosion process. Theoretically, these uncertainties can be modeled using a probabilistic approach. However, there are practical difficulties in identifying the probabilistic model for the deterioration process as the actual corrosion data are rather limited. Also, the dependencies between different random variables are often vaguely known and, thus, not included in the modeling. This paper proposes a probabilistic analysis framework for modeling the atmospheric corrosion of steel structures with incomplete information. The framework is based on the theory of imprecise probability and copula. Two examples are presented to illustrate the methodology. The role of epistemic uncertainties on structural reliability is investigated through the examples.